Local search for nonpreemptive multi-mode resource-constrained project scheduling - Rainer Kolisch; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
This paper addresses a general class of nonpreemptive resource-constrained project scheduling problems in which activity durations are discrete functions of committed renewable and nonrenewabe resources. We provide a 0-1 problem formulation and stress the importance of the outlined model by giving applications within production and operations management. Furthermore, we prove that even the problem to derive a feasible solution is NP-complete. As a consequence, solution procedures proposed so far suffer from severe drawbacks: Exact procedures can only solve very small instances to optimality, while heuristic solution approaches fail to generate feasible solutions when problems become highly resource-constrained. Hence, we propose a new local search methodology which first tries to find a feasible solution and second performs a single-neighbourhood search on the set of feasible mode-assignments. In order to evaluate the new procedura we perform a rigorous computational study on the ProGen benchmark-set which is available in the open literature. The experiment includes a comparison of our procedure with other recently proposed heuristics.
Keywords: 650; Resource-constrained project scheduling; Multiple execution modes; Nonrenewable resource constraints; NP-complete feasibility problem; Local search; Produktionssteuerung; Produktionskapazität; Theorie